Thermomechanical couplings in shape memory alloy materials - Soldatos, Dimitris; Triantafyllou, S.F.; Panoskaltsis, V.P. (Springer, 2017)
In this work we address several theoretical and computational issues which are related to the thermomechanical modeling of shape memory alloy materials. More specifically, in this paper we revisit a non-isothermal version of the theory of large deformation generalized plasticity which is suitable for describing the multiple and complex mechanisms occurring in these materials during phase transformations. We also discuss the computational implementation of a generalized plasticity based constitutive model and we demonstrate the ability of the theory in simulating the basic patterns of the experimentally observed behavior by a set of representative numerical examples.